Hyperpolarized [1,4-13C2]fumarate enables magnetic resonance-based imaging of myocardial necrosis - Miller, J; Lau, A; Nielsen, P; McMullen-Klein, G; Lewis, A; Jespersen, N; Ball, V; Gallagher, F; Carr, C; Laustsen, C; Bøtker, H; Tyler, D; et al. (Elsevier, 2017)
Objectives: The aim of this study was to determine if hyperpolarized [1,4–13C2]malate imaging could measure cardiomyocyte necrosis after myocardial infarction (MI). Background: MI is defined by an acute burst of cellular necrosis and the subsequent cascade of structural and functional adaptations. Quantifying necrosis in the clinic after MI remains challenging. Magnetic resonance-based detection of the conversion of hyperpolarized [1,4–13C2]fumarate to [1,4–13C2]malate, enabled by disrupted cell membrane integrity, has measured cellular necrosis in vivo in other tissue types. Our aim was to determine whether hyperpolarized [1,4–13C2]malate imaging could measure necrosis after MI. Methods: Isolated perfused hearts were given hyperpolarized [1,4–13C2]fumarate at baseline, immediately after 20 min of ischemia, and after 45 min of reperfusion. Magnetic resonance spectroscopy measured conversion into [1,4–13C2]malate. Left ventricular function and energetics were monitored throughout the protocol, buffer samples were collected and hearts were preserved for further analyses. For in vivo studies, magnetic resonance spectroscopy and a novel spatial-spectral magnetic resonance imaging sequence were implemented to assess cardiomyocyte necrosis in rats, 1 day and 1 week after cryo-induced MI. Results: In isolated hearts, [1,4–13C2]malate production became apparent after 45 min of reperfusion, and increased 2.7-fold compared with baseline. Expression of dicarboxylic acid transporter genes were negligible in healthy and reperfused hearts, and lactate dehydrogenase release and infarct size were significantly increased in reperfused hearts. Nonlinear regression revealed that [1,4–13C2]malate production was induced when adenosine triphosphate was depleted by >50%, below 5.3 mmol/l (R2 = 0.904). In vivo, the quantity of [1,4–13C2]malate visible increased 82-fold over controls 1 day after infarction, maintaining a 31-fold increase 7 days post-infarct. [1,4–13C2]Malate could be resolved using hyperpolarized magnetic resonance imaging in the infarct region one day after MI; [1,4–13C2]malate was not visible in control hearts. Conclusions: Malate production in the infarcted heart appears to provide a specific probe of necrosis acutely after MI, and for at least 1 week afterward. This technique could offer an alternative noninvasive method to measure cellular necrosis in heart disease, and warrants further investigation in patients.